Surveillance for West Nile Virus in Clinic-admitted Raptors, Colorado - Nemeth, Nicole (Centers for Disease Control and Prevention, 2007)
In 2005, 13.5% of clinic-admitted raptors in northern Colorado tested positive for West Nile virus (WNV). Clinic-admitted–raptor surveillance detected WNV activity nearly 14 weeks earlier than other surveillance systems. WNV surveillance using live raptor admissions to rehabilitation clinics may offer a novel surveillance method and should be considered along with other techniques already in use.